2019
DOI: 10.1042/bsr20181175
|View full text |Cite|
|
Sign up to set email alerts
|

Relationship between microRNA-27a and efficacy of neoadjuvant chemotherapy in gastric cancer and its mechanism in gastric cancer cell growth and metastasis

Abstract: Objective: The aim of the present study is to investigate the relationship between microRNA-27a (miR-27a) and the efficacy of neoadjuvant chemotherapy in gastric cancer (GC) and its mechanism in the growth and metastasis of GC cells. Methods: The expression of miR-27a in serum of 74 GC patients received neoadjuvant chemotherapy was detected by quantitative reverse transcriptase polymerase chain reaction (qRT-PCR). Clinical value and prognosis of miR-27a expression in predicting the efficacy of n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…In gastric cancer, there are several studies showing that miR-27a can be a good candidate as a biomarker for diagnosis and prognosis (30, 103, 105, 110, 111). From 164 gastric cancer patients and 127 normal people, miR-27a was identified to have a markedly higher confidence interval (0.879) than those of carcinoembryonic antigen (CEA) (0.503) and carbohydrate antigen 19-9 (CA19-9) (0.600), indicating that miR-27a can serve as a biomarker for gastric cancer diagnosis (102).…”
Section: Mir-27a In Clinical Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In gastric cancer, there are several studies showing that miR-27a can be a good candidate as a biomarker for diagnosis and prognosis (30, 103, 105, 110, 111). From 164 gastric cancer patients and 127 normal people, miR-27a was identified to have a markedly higher confidence interval (0.879) than those of carcinoembryonic antigen (CEA) (0.503) and carbohydrate antigen 19-9 (CA19-9) (0.600), indicating that miR-27a can serve as a biomarker for gastric cancer diagnosis (102).…”
Section: Mir-27a In Clinical Applicationsmentioning
confidence: 99%
“…In a novel study, the serum level of exosomal miR-27a was detected in 74 gastric cancer patients who received neoadjuvant chemotherapy by qRT-PCR, and the expression of miR-27a in the serum of gastric cancer patients decreased significantly after neoadjuvant chemotherapy. Gastric cancer patients who had a higher level of miR-27a tended to have tumor invasion and migration, indicating poor efficacy and prognosis after neoadjuvant chemotherapy (110). In another study, patients with upregulated miR-27a expression had significantly worse overall survival (OS) than patients with lower miR-27a expression ( P = 0.024), while a higher miR-27a expression level indicated resistance to fluoropyrimidine-based chemotherapy (105).…”
Section: Mir-27a In Clinical Applicationsmentioning
confidence: 99%
“…11 MiR-27a-3p is considered an oncogene because its overexpression is associated with a poor prognosis, as observed in patients with osteosarcoma or gastric cancer. 12,13 Some reports have found that miR-27a-3p enhances colon cancer progression and differentiation. 14 Besides, miR-27a-3p has been demonstrated to mediate chemoresistance of cancers such as leukemia, ovarian cancer, and hepatocellular carcinoma.…”
Section: Introductionmentioning
confidence: 99%
“…Accumulating evidence suggests that various non-coding regulatory miRNAs, including miR-27a, miR-196a-1, miR-208a and miR-206, also serve a prominent role in the activation of the Wnt/β-catenin signaling pathway by inactivating SFRP1, which induces GC cell proliferation, migration, invasion and metastasis (46,(75)(76)(77)(78)(79)(80). In addition, long non-coding RNAs (lncRNAs) are also emerging as key players in mediating this process (81).…”
Section: Discussionmentioning
confidence: 99%